Assisted Reproduction Divergence Between Law And Mental Health: About The Situation Of Infertile Couples In Peru - Roa-Meggo, Ysis (2015)
There is a divergence between the law, the use of assisted reproductive technologies and Mental Health in Peru. These three aspects should be consistent in their focus and concern for the welfare of the individual. However, a little sensitivity to the problems and the reality of infertile couples in Peru shows. In this article some aspects that related to mental health are discussed, involving infertility. Also, aspects of the existing law that may contribute to the deterioration of the mental health of people with infertility in Peru are required.